Sheikh Marouf Al-Nodhi's efforts in serving Islamic heritage - Ismail, Prof.Dr. Khaled Hussein (Sulaimani Journal for Humanities, 2024)
This research examines the life of a prominent Iraqi scholar, Sheikh Ma'ruf al-Nawdahi (d. 1254 AH), a leading figure in the Sulaymaniyah community, and his role in disseminating knowledge, culture, literature, and poetry. He lived in the late 12th and early 13th centuries AH, dedicating his life to learning and moving between libraries, mosques, schools, and scholarly circles. He was an author, publisher, preacher, reformer, and educator, leaving behind a rich scholarly legacy encompassing various fields of knowledge, including exegesis, hadith, jurisprudence, poetry, literature, and other sciences and arts. This research aims to introduce this eminent scholar, highlight his stature, contribute to the understanding of his works and poems, and uncover his legacy, which is found in Iraqi libraries. It also seeks to demonstrate the immense scholarly value of these works, which may assist researchers and specialists in exploring these topics related to the lives of the nation's scholars. The research is divided into an introduction, two main sections, and a conclusion. The introduction covers the political, cultural, and social conditions in Sulaymaniyah. The era of Sheikh Maarouf Al-Noudhi, and an introduction to the Sheikh - may God have mercy on him - and the first section deals with manuscript works, and the attention given to them by libraries and specialized scholars, and the second section deals with printed works and the attention given to them by specialized scholars, and the conclusion contains the most important results that I reached.
Keywords: Maruf; AlNawdhi; Sulaymaniyah Works